Dust Deposition Mechanism and Cleaning Strategy for Open Volumetric Air Receiver Based Solar Tower Sub-systems. (May 2015) - Singh, G.; Saini, D.; Yadav, N.; Sarma, R.; Chandra, L.; Shekhar, R.
Abstract: Desert regions like Rajasthan and Gujarat in India receives abundant solar energy. At the same time these regions are blessed with dust or sand. Solar thermal systems are one of the ways to harness this available energy. Open Volumetric Air Receiver based concentrated solar tower systems are being investigated for applications, like, metal processing. The dust deposition on sub-systems like, heliostat, porous receiver will hinder smooth operation of such a system. Considering this fact, aspects of dust deposition in porous absorber of the receiver and in heliostat are presented. In this direction, experiments and analyses are performed. This revealed that dust deposition on heliostat will be affected by its location among other parameters. The presented analysis shows the required free-stream air velocity for cleaning of such a mirror depending on particle size and location. Experiments on dust deposition in a single pore of an absorber, simulated by a thin and long glass tube of 1.3 mm diameter is presented. Furthermore, experiments on dust deposition in one porous absorber reveal its severe consequence. Finally, a strategy for collection of the removed dust particles from these pores is presented to avoid their passage to internals.